Peningkatan Kemampuan Bermain Drama dengan Bantuan Media Kartu Watak pada Siswa MTs Swasta Misbahul Ulum - Yulianda, Nisa'; Sundana, Lina (Tematik: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve students' drama playing skills assisted by character card media. This study uses a qualitative approach with the type of classroom action research. The research data were obtained from grade VIII students in the form of drama playing assessments by students while the sources of research data were students and teachers of MTs Swasta Misbahul Ulum. The data collection technique in the study used a test technique to obtain the results of students' drama playing skills with descriptive statistics as a data analysis technique. The results of the study showed that the average score of students at the pre-cycle stage (initial test) was 67.5 or 40% of students achieved a KKM score of 73, while the results of the first cycle of research, the average score was 75.43 with 70% of students achieving the KKM score. Furthermore, the results of the second cycle of research obtained an average score of 84.17 with 85% of students achieving the criteria for success of classroom action research (PTK).